Penerapan Jigsaw Untuk Meningkatkan Motivasi Belajar, Keterampilan Berpikir Kritis, Dan Berkomunikasi Pada Pembelajaran Ipa Siswa Kelas VA SD Strada Bhakti Wiyata II - Caecilia Ega Palmawati; Agus Santoso (Journal on Education, 2023)
Learning motivation, critical thinking and communication skills need to be improved. Based on the results of the observations in the 5th Grade of Strada Bhakti Wiyata II Elementary School, they were not optimal yet. The students seemed less enthusiastic in participating in the classroom because they did not get any proper appreciation after each lesson. Based on the problems found by researcher, it was necessary to conduct a Classroom Action Research design conducted on the 28 Grade 5 Elementary School students to analyze the developments of their learning motivation, critical thinking skills, and communication by applying the jigsaw type of the cooperative learning model in the Science class. Based on the results of the study, implemented in three cycles, it can be concluded that the application of the jigsaw type of the cooperative learning model could help the students improve their learning motivation, critical thinking skills and communication.